Perception of shift work, burnout and sleep disturbances: a study among call centre operators - Consiglio, Chiara; Tinelli, Erica (La Medicina del Lavoro, 2016)
Background: Shift work is often considered to be a factor  that can negatively affect health and sleep quality. However, it is usually considered as a structural factor of the job and not as a perception of a work demand. Objectives: The study aimed at analyzing the relationship between perception of shift work, burnout and sleep disturbances in a potentially stressful context, namely the call centre setting. Methods: Call centre operators (N=510) completed a questionnaire encompassing the following scales: perceptions of shift work, monotony, time pressure, exhaustion, cynicism and sleep disturbances. We conducted two hierarchical regressions in order to analyze the contribution of the perception of shift work on burnout dimensions (exhaustion and cynicism), beyond the contribution of socio-demographical variables, and of two specific job stressors for call centre operators, namely monotony and time pressure. The mediating role of exhaustion and cynicism between the perception of shift work and sleep disturbances was also explored. Results: The perception of shift work was associated with operators’ burnout, beyond the effect of socio-demographic variables and other job stressors. In addition, the relationship between the perception of shift work and sleep disturbances was fully mediated by exhaustion and partially mediated by cynicism. Conclusions: Perceived shift work may represent a risk factor for the health of call centre operators that should be monitored and possibly managed through specific organizational interventions.